Shades of White Flight : Evangelical Congregations and Urban Departure - Mulder, Mark T., 1973- (Book collections on Project MUSE., 2015)
Since World War II, historians have analyzed a phenomenon of zwhite flighty plaguing the urban areas of the northern United States. One of the most interesting cases of zwhite flighty occurred in the Chicago neighborhoods of Englewood and Roseland, where seven entire church congregations from one denomination, the Christian Reformed Church, left the city in the 1960s and 1970s and relocated their churches to nearby suburbs. In Shades of White Flight, sociologist Mark T. Mulder investigates the migration of these Chicago church members, revealing how these churches not only failed to inhibit white flight, but actually facilitated the congregations' departure. Using a wealth of both archival and interview data, Mulder sheds light on the forces that shaped these midwestern neighborhoods and shows that, surprisingly, evangelical religion fostered both segregation as well as the decline of urban stability. Indeed, the Roseland and Englewood stories show how religion--often used to foster community and social connectedness--can sometimes help to disintegrate neighborhoods. Mulder describes how the Dutch CRC formed an insular social circle that focused on the local church and Christian school--instead of the local park or square or market--as the center point of the community. Rather than embrace the larger community, the CRC subculture sheltered themselves and their families within these two places. Thus it became relatively easy--when black families moved into the neighborhood--to sell the church and school and relocate in the suburbs. This is especially true because, in these congregations, authority rested at the local church level and in fact they owned the buildings themselves. Revealing how a dominant form of evangelical church polity--congregationalism--functioned within the larger phenomenon of white flight, this book lends new insights into the role of religion and how it can affect social change, not always for the better. (Publisher).